Quantum computers, quantum computing, and quantum thermodynamics - Cleri, Fabrizio (Frontiers in Quantum Science and Technology, 2024)
Quantum thermodynamics aims at extending standard thermodynamics and non-equilibrium statistical physics to systems with sizes well below the thermodynamic limit. A rapidly evolving research field, which promises to change our understanding of the foundations of physics, while enabling the discovery of novel thermodynamic techniques and applications at the nanoscale.Thermal management has turned into a major obstacle in pushing the limits of conventional digital computers, and could likely represent a crucial issue also for quantum computers. The practical realization of quantum computers with superconducting loops requires working at cryogenic temperatures to eliminate thermal noise; ion-trap qubits need as well low temperatures to minimize collisional noise; in both cases, the sub-nanometric sizes also bring about thermal broadening of the quantum states; and even room-temperature photonic computers require cryogenic detectors. A number of thermal and thermodynamic questions therefore take center stage, such as quantum re-definitions of work and heat, thermalization and randomization of quantum states, the overlap of quantum and thermal fluctuations, and many other, even including a proper definition of temperature for the small open systems constantly out of equilibrium that are the qubits. This overview provides an introductory perspective on a selection of current trends in quantum thermodynamics and their impact on quantum computers and quantum computing, with a language accessible also to postgraduate students and researchers from different fields.